2021
DOI: 10.1186/s40168-021-01049-2
|View full text |Cite
|
Sign up to set email alerts
|

Specific and conserved patterns of microbiota-structuring by maize benzoxazinoids in the field

Abstract: Background Plants influence their root and rhizosphere microbial communities through the secretion of root exudates. However, how specific classes of root exudate compounds impact the assembly of root-associated microbiotas is not well understood, especially not under realistic field conditions. Maize roots secrete benzoxazinoids (BXs), a class of indole-derived defense compounds, and thereby impact the assembly of their microbiota. Here, we investigated the broader impacts of BX exudation on r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 67 publications
2
46
0
Order By: Relevance
“…First, if BX-feedbacks would be relevant in agriculture, they should also occur in other soils. This seemed possible as it is well-known that PSF happen in different soil types and with different microbiota pools (Bergmann et al, 2016;Smith-Ramesh & Reynolds, 2017), and we also knew that different soils have BXsensitive microbes (Cadot et al, 2021). Therefore, we asked (a) whether BX-feedbacks would also occur in other soils.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, if BX-feedbacks would be relevant in agriculture, they should also occur in other soils. This seemed possible as it is well-known that PSF happen in different soil types and with different microbiota pools (Bergmann et al, 2016;Smith-Ramesh & Reynolds, 2017), and we also knew that different soils have BXsensitive microbes (Cadot et al, 2021). Therefore, we asked (a) whether BX-feedbacks would also occur in other soils.…”
Section: Introductionmentioning
confidence: 99%
“…Cadot et al (2021) we investigated the general structuring of BX exudation on the root and rhizosphere microbiota and we found little overlap among BX-sensitive microbes in different field soils. This implies that different sets of BX-sensitive microbiotas can trigger similar feedback effects and that there is a functional overlap among them in different soils.With this study, we now know that BX-feedbacks on maize function in the clay loam soil Changins and the loam soil Reckenholz, but not the silt loam soil Q-Matte.…”
mentioning
confidence: 98%
“…Recently research found that the host plant factors shape the plant-association microbiota community, those secrete signals to recruit specific microbiota while generating molecules that are toxic to others (Macabuhay et al, 2021, Thoms et al, 2021. Such as, plant special metabolites triterpenes, coumarin, flavonoid and benzoxazinoid are key compounds modulating plant microbiota composition (Cadot et al, 2021, Cotton et al, 2019, Harbort et al, 2020, Hu et al, 2018, Kudjordjie et al, 2019, Pang et al, 2021, Schütz et al, 2019, and root secretes coumarin to against pathogens and impact the assembly of rhizosphere microbiota (Stringlis et al, 2018). Moreover, the important of plant metabolites or root exudates in defense pathogens and maintain microbial homeostasis in the rhizosphere is increasingly recognized, such as volatile organic compounds, tryptophan, phytohormones and camalexin (Hammerbacher et al, 2019, Koprivova et al, 2019, Macabuhay et al, 2021, Pang et al, 2021, Sharifi et al, 2018, Stassen et al, 2020, Wolinska et al, 2021.…”
Section: Discussionmentioning
confidence: 99%
“…In the maize-faba bean intercropping system, legume roots stimulate the expression of Bx genes necessary for the biosynthesis of the phytoalexins DIMBOA (2,4-dihydroxy-7-methoxy-1,4-benzoxazin-3-one) and MBOA (6-methoxy-2benzoxazolinone) in maize (Yan et al, 2014). Microbial diversity from the rhizosphere of maize deficient in DIMBOA or MBOA differs from that of the wild type, therefore, maize metabolites may also limit the growth of soil microbes (Cotton et al, 2019;Cadot et al, 2021). Phytoalexins produced by milpa system has not been determined; however, we detected overexpression of Ch24-10 genes rmrA and rmrB that has been described in Rhizobium etli as being important in the tolerance to the phytoalexin phaseolin and flavonoids of beans (González-Pasayo and Martínez-Romero, 2000).…”
Section: Discussionmentioning
confidence: 99%